2015
DOI: 10.1590/1809-4430-eng.agric.v35n2p266-279/2015
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural networks as an alternative to volumetric water balance in drip irrigation management in watermelon crop

Abstract: Precision irrigation seeks to establish strategies which achieve an efficient ratio between the volume of water used (reduction in input) and the productivity obtained (increase in production). There are several studies in the literature on strategies for achieving this efficiency, such as those dealing with the method of volumetric water balance (VWB). However, it is also of great practical and economic interest to set up versatile implementations of irrigation strategies that: (i) maintain the performance ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…They concluded that an ANN is an efficient method and can be a substitute for the volumetric balance method. Further, they reported that the ANN method has ease of implementation and speed of response when doing the computational analysis (Rocha Neto et al, 2015). Umair and Usman (2010) used ANN technology to study effective irrigation scheduling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that an ANN is an efficient method and can be a substitute for the volumetric balance method. Further, they reported that the ANN method has ease of implementation and speed of response when doing the computational analysis (Rocha Neto et al, 2015). Umair and Usman (2010) used ANN technology to study effective irrigation scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…An artificial neural network (ANN) is another modern approach used in different regions of the world to manage water resources. In a study conducted by Rocha Neto et al (2015), an ANN was used to estimate the irrigation period for a watermelon crop. They concluded that an ANN is an efficient method and can be a substitute for the volumetric balance method.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring a certain degree of interpretability is as important as accuracy so it could be understood by any person if needed, to accomplish that aim the use of an intuitive Mamdani fuzzy inference systems (configured by multiple conditional rule sets) could be a suitable solution [7,8]. Neural networking, usually used in black box systems, is a technology that also contributes to the study of the dynamic behavior of climate; in the agricultural field, its application eases the water use balance in irrigation [9,10]. Furthermore, computer models capable of predicting climate behavior and the impact of greenhouse gases on earth's temperature were developed some decades ago, however, these models only analyze the CO2 related variables [11], presence, and concentration, when research has shown there are many others involved [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the application of computer Engenharia Agrícola, Jaboticabal, v.41, n.4, p.418-426, jul./aug. 2021 modeling has been widely used, such as fuzzy logic and neural networks, both in agriculture (Rocha Neto et al, 2015, Putti et al, 2017a, Putti et al, 2017b and in the areas of animal comfort (Schiassi et al, 2015, Hernández Julio et al, 2015, Mirzaee-Ghalehv et al, 2015, Bahuti, et al, 2018, Lourençoni, et al, 2019a, Lourençoni, et al, 2019b, Abreu et al, 2020.…”
Section: Introductionmentioning
confidence: 99%